English for Specific Purposes: Incessant Self-education of its Lecturers - Stojković, Nadežda; Kenny, Nalan; Antić, Zorica; Piršl, Danica (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2016)
This paper draws attention to the particularities of the specially demanding positions of lecturers of English for Specific Purposes (ESP) in terms of the need for their incessant self-education in two areas of expertise. Teaching ESP is the most performativity-oriented form of English Language Teaching (ELT). The widespread presence of ESP implies its high relevance for the interested learners. Here lies an unusually demanding situation for a linguist. There are usually no ready-made ESP courses that can meet a group of students’ needs that are unique. This leaves lecturers on their own to develop appropriate teaching materials and courses. In today’s competitive world of science and business domains, the ESP lecturer needs to constantly know the developments in linguistics and developments in the field they did not receive their primary education in. These must be done to ensure learners ability to be successful on a global level.